Creative Source or the End of the Line? - Barter, William (Farol, 2024)
In December 2009, I returned from a season in Rio de Janeiro that, for many reasons, had been a rich learning experience. I said to myself: I don’t want to work in marketing anymore! As much as I loved my job, and I still do, at that time, something instinctive awakened in me, as if the very future of the profession was compromised. Technology was taking over all creative layers, speeding up processes and making everything extremely "easy".